A technical perspective of knowledge management in collaborative software maintenance environment - Mohd Nor, Mohd Zali; Abdullah, Rusli (Universiti Utara Malaysia, 2008)
Knowledge management (KM) is critical in Software Maintenance (SM) organizations to provide an environment for creating and sharing knowledge. SM environment is complex, knowledge-driven and highly collaborative. Issue such as inadequate knowledge is still regarded as a major challenge in SM. To find out more on the above limitation in term of technical perspective, we study the activities of a maintenance organization and conducted a survey and discussion. Based on the results, we conclude that domain and technical knowledge are important to maintainers, but are often not available. Also, usefulness of tools to acquire and share knowledge are limited, mainly due to lack of integration between tools.